1999
DOI: 10.1016/s0014-5793(99)00197-0
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the site for the nucleotide effectors ofEscherichia colicarbamoyl phosphate synthetase using site‐directed mutagenesis

Abstract: Replacement by alanine of Ser-948, Thr-974 and Lys-954 of Escherichia coli carbamoyl phosphate synthetase (CPS) shows that these residues are involved in binding the allosteric inhibitor UMP and the activator IMP. The mutant CPSs are active in vivo and in vitro and exhibit normal activation by ornithine, but the modulation by both UMP and IMP is either lost or diminished. The results demonstrate that the sites for UMP and IMP overlap and that the activator ornithine binds elsewhere. Since the mutated residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…IMP binding has been localized to domain D by photolabeling (33), site-directed mutagenesis (34 -39), and crystal structure analysis (28). UMP binding has also been localized to domain D by photolabeling (40) and site-directed mutagenesis (35)(36)(37)(38)(39). Studies with a number of UMP and IMP 2 Primers (with mutated residues in bold): P1, 5Ј-AAGTACCAACT-AGTTCCATGTACC-3Ј; P2, 5Ј-GGCCGCTCTAAAGCTTGTGGATCC-3Ј; P3, 5Ј-GGGCAGCAACTAGTCCATGAAG-3Ј; P4, 5Ј-CTTCATGGA-CTAGTTGCTGCCC-3Ј; P5, 5Ј-GCAGCTGGGCAGCAACAACTTCCAT-GTACCACTACC-3Ј; P6, 5Ј-GGTAGTGGTACATGGAAGTTGT-TGCTGCCCAGCTGC-3Ј.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IMP binding has been localized to domain D by photolabeling (33), site-directed mutagenesis (34 -39), and crystal structure analysis (28). UMP binding has also been localized to domain D by photolabeling (40) and site-directed mutagenesis (35)(36)(37)(38)(39). Studies with a number of UMP and IMP 2 Primers (with mutated residues in bold): P1, 5Ј-AAGTACCAACT-AGTTCCATGTACC-3Ј; P2, 5Ј-GGCCGCTCTAAAGCTTGTGGATCC-3Ј; P3, 5Ј-GGGCAGCAACTAGTCCATGAAG-3Ј; P4, 5Ј-CTTCATGGA-CTAGTTGCTGCCC-3Ј; P5, 5Ј-GCAGCTGGGCAGCAACAACTTCCAT-GTACCACTACC-3Ј; P6, 5Ј-GGTAGTGGTACATGGAAGTTGT-TGCTGCCCAGCTGC-3Ј.…”
Section: Resultsmentioning
confidence: 99%
“…The chCPS response to ornithine was not surprising because ornithine is known to bind at the domain C/D interface (29,30,35,36,42,43), and because domain C of chCPS is derived from the ornithineresponsive eCPS. However, the chCPS response to UMP was unexpected because the binding site for pyrimidine nucleotides resides entirely in domain D (29,30,(35)(36)(37)(38)(39)(40). We therefore screened a second pyrimidine nucleotide, UTP, which is known to inhibit eCPS but only at 100 times higher concentrations than required for UMP (3).…”
Section: Screening Of Potential Allosteric Effectors With Chcps-mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies performed with analogs of UMP and IMP already indicated that these antagonistic nucleotide effectors may bind the same or overlapping sites, but that this site is distinct from the ornithine binding site (Boettcher and Meister 1981, 1982; Mora et al 1999; Fresquet et al 2000; Braxton et al 1999). The binding of UMP and ornithine essentially affect the binding of the second Mg 2+ ATP molecule (Braxton et al 1992, 1999).…”
Section: Allosteric Regulation Of Cpsase Activitymentioning
confidence: 99%
“…The isolated domains form homodimers that catalyze both ATP-dependent partial reactions and the overall synthesis of carbamoyl phosphate from bicarbonate, NH 3 , and two ATP molecules. The only apparent functional difference between the CPS.A and CPS.B dimers is that the latter is subject to allosteric control because effectors bind to the regulatory subdomain (21)(22)(23)(24)(25)(26)(27) at the extreme carboxyl end of CPS.B.…”
mentioning
confidence: 99%